Shocks and solitons in collisional dense laser produced plasmas. (1st April 2022) - Shilpa, S; Pai, Divya D; Michael, Manesh; Venugopal, C; Gopinath, Pramod
Abstract: The characteristics of nonlinear electron-acoustic waves such as shocks and solitons, are investigated in a three component, dense laser produced plasma consisting of ions and two distinct groups of electrons, using the quantum hydrodynamic model and the standard reductive perturbation method. The modified Korteweg-deVries (mKdV) and Korteweg-deVries-Burgers (KdVB) equations have been derived for the electron-acoustic waves in the plasma. The dependence of both shocks and solitons on various parameters has been extensively studied. It is observed that whenever the density crosses the limit from the classical to the quantum range, the effective potential remains invariant for the solitary profiles; but shows a slight variation for the shock profiles. The collisional effect plays a significant role in the dissipation of solitary waves and the dissipation is larger for higher values of collision frequencies. The results obtained could prove helpful for understanding the parametric dependence of nonlinear waves in highly intense laser plasma interactions.